USING CARTOONS AND ANIMATED STORIES TO DEVELOP LISTENING AND COMPREHENSION SKILLS - Eshniyozova Jasmina Jo’rabekovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This work examines the role of cartoons and animated stories in developing listening and comprehension skills for language learners. By analyzing how these  media  integrate  both  visual  and  auditory  elements,  the  study  highlights  their potential to engage learners through context-rich narratives, clear speech patterns, and frequent repetition of vocabulary. The use of animated content helps learners connect words  with  actions,  emotions,  and  settings,  providing  a  deeper  understanding  of language.  Additionally,  the  study  underscores  the  importance  of  engaging  and interactive content, which not only aids comprehension but also motivates learners to stay actively involved in the language learning process. The paper further explores how cartoons of varying genres and complexity cater to different learner levels, offering a versatile tool for both children and adults. Ultimately, this research provides insights into  how  animated  stories  can  serve  as  a  fun  and  effective  educational  resource, enhancing the listening skills and overall language proficiency of learners. Abstract: This study explores the use of cartoons and animated stories as tools for enhancing listening and comprehension skills. These mediums are examined for their ability to provide contextual support through visual cues, engaging narratives, and natural speech patterns, all of which contribute to improved language acquisition. The study  emphasizes  the  benefits  of  exposure  to  authentic  conversational  language, repeated vocabulary, and active listening strategies. Additionally, the use of cartoons in various genres and levels offers a flexible, enjoyable learning experience, making it an  ideal  method  for  both  children  and  adults.  The  effectiveness  of  cartoons  as  a language learning tool is analyzed through examples of popular animated shows and their impact on comprehension, retention, and engagement.